INDONESIAN HIGH SCHOOL STUDENTS’ DIFFICULTIES IN UNDERSTANDING ENGLISH TEXT - Selvia Mardiani; Jismulatif; Erni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to find out students’ difficulties in understanding descriptive texts at the second year of SMAN 3 Langgam, Riau. This was quantitative research. The population of this research was all students at the second year of SMAN 3 Langgam. The samples of this research were 34 students at XI IIS 1 class who were selected by using the cluster-random-sampling technique. The data were collected by using tests and questionnaires. The test consisted of 40 questions, and the questionnaire consisted of 25 questions. The percentage of the answers of the reading test revealed eight components of reading comprehension. Six of them were categorized as high level difficult questions, including difficulties in identifying vocabulary, generic structure, factual information, reference, language features, and social functions. Two of them were categorized as medium level, including difficulties in identifying the main idea and inference. Based on the result of the questionnaire, the students found difficulties in understanding descriptive texts due to the intrinsic and extrinsic factors. The intrinsic factors were limited vocabulary knowledge, problems in recalling information, lack of familiarity with the subject topic, lack of reading fluency, and problems in processing information after reading. Meanwhile, the extrinsic factors were weak verbal reasoning, problems in understanding the text because of the level of the text, and inadequate use of reading strategies in the teaching and learning process.